SPE Eastern Regional Meeting 2002
DOI: 10.2118/78691-ms
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Carbon Dioxide Sequestration/ECBM Production in Coal Seams: Effects of Coal Properties and Operational Parameters

Abstract: Carbon dioxide sequestration is a promising technology for reducinganthropogenic greenhouse gas emissions while fossil fuels are still being used.The costs associated with CO2 sequestration are often high; however, in certain circumstances (e.g., enhanced oil recovery) these costs can be morethan offset by the benefits of additional incremental hydrocarbon production.Primary production of coalbed methane is a well-developed technology, butsecondary production, through the injection of CO2 or N2has undergone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…For higher permeabilities, lower injection pressures are better. As our previous studies 22 have shown, higher injection pressures cause higher average reservoir pressures, which allow more CO 2 to be sorbed per unit volume of coal. For the case when there are no credits, more CO 2 injection worsens the economics, and therefore those projects with higher reservoir pressure perform worse.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…For higher permeabilities, lower injection pressures are better. As our previous studies 22 have shown, higher injection pressures cause higher average reservoir pressures, which allow more CO 2 to be sorbed per unit volume of coal. For the case when there are no credits, more CO 2 injection worsens the economics, and therefore those projects with higher reservoir pressure perform worse.…”
Section: Methodsmentioning
confidence: 65%
“…The length of injectors was kept constant in this study, at 735 ft. This value represents an optimum tradeoff value between methane production and CO 2 sequestration 22 . In a previous study we found that small variations of the injector lengths do not have a large influence on the economics of the project 36 .…”
Section: Methodsmentioning
confidence: 99%
“…8 The present authors have previously examined the performance of this well configuration in a series of papers. [18][19][20][21] That work served to identify reservoir and operational parameters that have important effects on project performance. These parameters can be divided roughly into two groups: those that determine the theoretical maximum amount of methane that can be produced and the maximum amount of carbon dioxide that can be sequestered, and those that determine the fraction of the theoretical maximum that can be obtained in an actual project.…”
Section: Project Backgroundmentioning
confidence: 99%
“…This is consistent with other published results for the Wyodak coals. 2,5 The sorption time was related to the simulation input parameters describing the matrix-fracture coupling and the gas diffusion coefficient using the relationships presented by Sams, et al 6 The remaining properties critical to obtaining a successful history match with the simulation model were the coal transmissivity and storativity variables (Ί, k, C f ), and the influence of the surrounding regional aquifer. Measured data for coal compressibility or porosity were not available.…”
Section: Calibration Of the Modelmentioning
confidence: 99%